The empty grave - Stroud, Jonathan (Stroud, Jonathan. Lockwood & Co., 2017)
"With the help of some unexpected, and rather ghostly, allies, Lockwood & Co. must battle their greatest enemy yet, as they move ever closer to the moment when the earth-shattering secret of 'the problem' will finally be revealed"--